2017
DOI: 10.1186/s10397-017-1001-9
|View full text |Cite
|
Sign up to set email alerts
|

Oophoropexy for ovarian torsion: a new easier technique

Abstract: BackgroundOophoropexy for ovarian torsion is easy to be done by many tools either suturing to the lateral pelvic wall, plication of the ovarian ligament or even fixation to the back of the uterus, but it is little bit difficult to do it for pregnant women with less manipulation.ObjectiveWe propose that using trocar site closure needle can be easier and faster technique to do this. To assess the feasibility of using the trocar site closure needle to do oophoropexy in ovarian torsion and its possible applicabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…7,8 Hysteroscopic transcervical resection of myoma (TCRM) also has some limitations, such as the potential for conversion to laparotomy and incomplete intraoperative resection in patients with larger or previously myomectomised submucosal myomas. 9,10 Many studies have been performed to compare the clinical outcomes of abdominal hysterectomy and laparoscopic or hysteroscopic surgery. 11 However, no final conclusions have been reached regarding the clinical outcomes, advantages, and disadvantages of laparoscopic and hysteroscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Hysteroscopic transcervical resection of myoma (TCRM) also has some limitations, such as the potential for conversion to laparotomy and incomplete intraoperative resection in patients with larger or previously myomectomised submucosal myomas. 9,10 Many studies have been performed to compare the clinical outcomes of abdominal hysterectomy and laparoscopic or hysteroscopic surgery. 11 However, no final conclusions have been reached regarding the clinical outcomes, advantages, and disadvantages of laparoscopic and hysteroscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent adnexal torsion can also be prevented by adnexal detorsion and shortening the utero-ovarian ligament. [ 15 , 21 ] Seven cases of ovarian torsion were reported by Hosny et al [ 22 ] ; 2/7 cases had OHSS, and 50% of the patients showed clinical symptoms and hemorrhagic cysts. Fortunately, there was no recurrence in these 2 patients, who underwent detorsion and oophoropexy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Detorsion can be performed in early stages in normal looking adnexa, so that the blood supply is resumed, as done by Pinkert in an 18 year old female with an edematous ovary and haematosalpinx. 7,8 In adolescents, treatment can be done conservatively with aspiration of the hydrosalpinx, but if it recurs, salpingectomy is recommended to prevent detorsion.…”
Section: Discussionmentioning
confidence: 99%